Moral evaluation in critical discourse analysis. Issue 2 (15th March 2018) - van Leeuwen, Theo
ABSTRACT: Discourse analysis can reveal what texts leave out, and how texts transform and evaluate the social realities they represent but critical discourse analysis must also evaluate the findings of discourse analysis, and, this paper argues, this cannot be done on discourse-internal grounds alone. To develop this argument, the paper will first discuss how critical discourse analysts might establish whether mis representations have taken place, and then how they might assess whether such misrepresentations legitimate and promote unacceptable forms of inequality, in other words, how discourses might be morally evaluated. Special reference is made to the issue of 'marriage equality' as it has recently played out in Australia.